ANALISIS KEKUATAN HELIDECK SANTOS SANGU PT. McDERMOTT INDONESIA - Anwar Anwar; Hariyono Ismail (Construction and Material Journal, 2023)
Offshore building structures are buildings commonly used for oil and gas exploitation activities. The distance is quite far from the coastal area, it is necessary to support transportation facilities for the mobility of offshore structures such as ships and helicopters. To support this mobilization activity, a helicopter landing medium is needed, namely the helideck. This study aims to identify the shock loads that occur on the helideck and calculate the strength of the helideck santos sangu PT.McDermott Indonesia. This study used data from PT.McDermott Indonesia on one of the projects located in Block 16, Bangladesh. The helicopter data used in this study was a jet-A1 type helicopter with a maximum weight of 5307 Kg. The results showed that the value of the helicopter dynamic load on a normal landing was 10348.65 Kg with a working stress of 62163.41 N/mm2 and had an interaction ratio (IR) = 0.35, while for an emergency landing the dynamic load was 1724.75 Kg, the working stress was 103606.45 N/mm2, interaction ratio (IR)= 0.59.